ILLUMINATO AIGUINO AND THE PERSISTENCE OF COMMIXTURE IN LATE SIXTEENTH-CENTURY ITALIAN MUSIC THEORY - Iafelice, Carlos Cascarelli [UNESP] (My University, 2021)
This study aims to demonstrate the detailed treatment of modal commixture adopted by Illuminato Aiguino in his two treatises, namely La Illuminata of Tutti i Tuoni di Canto Fermo (Venice, 1562) and Il Tesoro Illuminato di Tutti i Tuoni di Canto Figurato (Venice, 1581), from an alternative perspective compared to the theoretical codification approach that underpins Zarlino's twelvefold system (after Glarean). The persistence of an expanded modal proposal of the octonary tradition post-Zarlino can also denote an option for the codification of sound spaces of polyphonic pieces with characteristics that are understood to be modally inconsistent in view of the eight-mode system. Therefore, in the final part of this study, two motets cited by Zarlino as belonging to Mode 9 and 10 (Sancta et immaculata Virginitas by Morales and Flete oculi by Willaert, respectively) will be observed from the prism of Aiguino's theory making it possible to compare and contrast from a perspective of both modal systems identifying their differences and similarities.
Keywords: history of music theory; Iluminato Aiguino; modal commixture; modal theory; music analysis